2003
DOI: 10.1161/01.cir.0000060533.79248.0c
|View full text |Cite
|
Sign up to set email alerts
|

Increased Plasma Natriuretic Peptide Levels Reflect Symptom Onset in Aortic Stenosis

Abstract: Background-The onset of symptoms is a critical point in the natural history of aortic stenosis and the cardinal indication for valve replacement. This study assessed the associations between natriuretic peptide levels, disease severity, and cardiac symptoms in aortic stenosis. Methods and Results-Seventy-four patients with isolated aortic stenosis underwent independent assessment of symptoms, transthoracic echocardiography, and measurement of plasma levels of atrial natriuretic peptide, brain natriuretic pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
145
2
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(161 citation statements)
references
References 44 publications
(42 reference statements)
10
145
2
4
Order By: Relevance
“…However, to our knowledge, NP has not been associated with impaired LA remodeling and the occurrence of late postoperative AF previously. We have firstly reported that N-ANP levels and age, which was lower in our small patient cohort compared to previous reports [2, 15], were independent predictors of late AF following surgery for AS. In addition, patients with postoperative AF episodes had significantly higher preoperative LA min and LA max levels and longer symptom duration compared to those without, though they were not found to be independent predictors.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…However, to our knowledge, NP has not been associated with impaired LA remodeling and the occurrence of late postoperative AF previously. We have firstly reported that N-ANP levels and age, which was lower in our small patient cohort compared to previous reports [2, 15], were independent predictors of late AF following surgery for AS. In addition, patients with postoperative AF episodes had significantly higher preoperative LA min and LA max levels and longer symptom duration compared to those without, though they were not found to be independent predictors.…”
Section: Discussioncontrasting
confidence: 54%
“…ANP is cleared by enzymes, which are extensively expressed in the lung, kidney and the vascular wall [11]. Previously, ANP levels have been evaluated in AS patients and found to mirror symptom onset [15]. In addition, temporal changes in ANP values have been evaluated separately [6].…”
Section: Discussionmentioning
confidence: 99%
“…BNP levels are elevated in aortic stenosis and are linearly related to symptoms [92]. Furthermore, BNP values above 190 pg/ml portend a much worse outcome, suggesting that BNP may be useful in identifying subgroups of patients with aortic stenosis that may benefit from aortic valve replacement [93].…”
Section: Cardiac Amyloidosismentioning
confidence: 99%
“…45,47 In asymptomatic severe AS, baseline BNP levels are predictive of an abnormal blood pressure response to exercise, earlier symptom onset, and increased risk of re-hospitalization due to HF, need for AVR, and mortality. [48][49][50][51][52] Of note, most of these studies excluded patients with depressed LV function and/or concomitant valve disease which might otherwise cause elevated natriuretic peptide levels. 53,54 Hence, the results and conclusions of these studies apply to AS patients with otherwise normal cardiac structure and function.…”
Section: B-type Natriuretic Peptidesmentioning
confidence: 99%